2006
DOI: 10.1007/s00198-006-0259-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of treatment with a thiazide diuretic for 4 years on bone density in normal postmenopausal women

Abstract: Hydrochlorothiazide produces small positive benefits on cortical bone density that are sustained for at least the first 4 years of treatment. They provide a further option in the prevention of postmenopausal bone loss, especially for women with hypertension or a history of kidney stones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
57
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(67 citation statements)
references
References 30 publications
7
57
1
2
Order By: Relevance
“…They demonstrated that thiazid diuretics altered the intracellular calcium regulation in rat osteoblastlike cells, thus providing evidence of direct effects of thiazid diuretics on bone cells. In RCTs, thiazid diuretics have been associated with a modest positive effect on bone mineral density at the hip , Bolland et al, 2007, Reid et al, 2000. In accordance with these studies, thiazid diuretic use has been associated with reduced hip fracture rates as reported in observational studies (Reid et al, 2000, Bolland et al, 2007, Rejnmark et al, 2005b, Herings et al, 1996, Schoofs et al, 2003.…”
Section: Thiazid Diuretic Usesupporting
confidence: 64%
See 2 more Smart Citations
“…They demonstrated that thiazid diuretics altered the intracellular calcium regulation in rat osteoblastlike cells, thus providing evidence of direct effects of thiazid diuretics on bone cells. In RCTs, thiazid diuretics have been associated with a modest positive effect on bone mineral density at the hip , Bolland et al, 2007, Reid et al, 2000. In accordance with these studies, thiazid diuretic use has been associated with reduced hip fracture rates as reported in observational studies (Reid et al, 2000, Bolland et al, 2007, Rejnmark et al, 2005b, Herings et al, 1996, Schoofs et al, 2003.…”
Section: Thiazid Diuretic Usesupporting
confidence: 64%
“…In RCTs, thiazid diuretics have been associated with a modest positive effect on bone mineral density at the hip , Bolland et al, 2007, Reid et al, 2000. In accordance with these studies, thiazid diuretic use has been associated with reduced hip fracture rates as reported in observational studies (Reid et al, 2000, Bolland et al, 2007, Rejnmark et al, 2005b, Herings et al, 1996, Schoofs et al, 2003. However, these potential positive effects of thiazid diuretics on bone health were modest and therefore a long-term treatment period may be needed to improve implant fixation and thereby reduce the risk of revision.…”
Section: Thiazid Diuretic Usementioning
confidence: 60%
See 1 more Smart Citation
“…11,[20][21][22] These findings might be partly explained by the threefold increased risk of women to develop ACE-inhibitor-related cough or potential beneficial effects of thiazides on bone density in postmenopausal women. 23,24 Furthermore, safety concerns in prescribing ACEs to women of childbearing age might have contributed to the lower number of ACE-inhibitor prescriptions. However, only a small proportion of women aging 18-40 years were included (2.5%), and about two-thirds of women were 460 years old.…”
Section: Discussionmentioning
confidence: 99%
“…Use of calcium supplements [31,32] and health status [33] (excellent/very good/good/fair/poor), were also included. Additionally, the use of estrogen [34] and other medications known to modify bone mineral density or fracture risk (statins [35], loop diuretics [36], thiazides [37], thyroid hormones [38]), and corticosteroids [39]) were included. Participants who were using bisphosphonates or selective estrogen receptor modulators (SERMs) were excluded.…”
Section: Covariatesmentioning
confidence: 99%